Causal effects of fatty acids on atopic dermatitis: A Mendelian randomization study - Lin, Jia-Ying; Ma, Liang-Juan; Yuan, Jin-Ping; Yu, Pei; Bai, Bing-Xue (Frontiers in Nutrition, 2023)
Background Some evidence of fatty acids abnormalities in patients with atopic dermatitis (AD) was reported and the beneficial effects of their supplementation have also been reported. However, there is still substantial controversy on the correlation between fatty acids and AD. This study therefore aimed to determine whether fatty acids levels are causally related to atopic dermatitis using Mendelian randomization method. Methods Exposure-outcome relationships between fatty acids levels and AD were mainly evaluated by the inverse variance weighted (IVW) two sample Mendelian randomization (MR) method using fatty acids levels and AD genome wide association study (GWAS) results. GWAS results were available for European (fatty acids) and European (AD) ancestry samples. Weighted median, weighted mode, and MR Egger regression methods were also used as sensitivity analyses. To address underlying mechanisms, further analyses were performed using instruments associated with the FADS genes. Multivariable MR (MVMR) was also applied to estimate direct effects of omega-3(n-3) fatty acids on AD, independent of omega-6(n-6) fatty acids, monounsaturated fatty acids, saturated fatty acids. Results MR analyses indicated that n-3 fatty acids levels were associated with lower risk of AD (n-3 ORIVW: 0.92, 95% confidence interval [CI]: 0.87-0.98; P=0.01). Besides, long-chain n-3 fatty acids docosahexaenoic acids [DHA]）levels were associated with lower risk of AD（DHA ORIVW: 0.91, 95% CI: 0.84-0.98; P=0.02). we performed multivariable MR analysis adjusting for variables within the same category. The effect of n-3 fatty acids levels on AD was robust and the effect estimates were consistent with initial MR analysis. The results were robust in sensitivity analyses and outliers-corrected MR analyses after controlling horizontal pleiotropy were still robust. The FADS single-SNP analyses also indicated that n-3 fatty acids levels were associated with lower risk of atopic dermatitis, highlighting the significance of the FADS gene in the fatty acids synthesis pathway in the development of AD. Conclusion These data suggest that n-3 fatty acids are associated with lower risk of AD. Risk prediction tools based on the level of n-3 fatty acids may be a valuable approach to improve screening and primary prevention of AD.